Spatial Based Economic Valuation of Coastal Area in Bontang - Erwan Sulistianto; Eva Anggraini; Agus Sadeli; Achmad Fahrudin; Tridoyo Kusumastanto (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
Coastal areas have an important role in economic development. Development activities carried out on land and at sea can put pressure on ecosystems in coastal areas, thereby reducing the quality of the ecosystem services provided. Understanding the impact of development on ecosystems in coastal areas requires an economic assessment in order to provide input in the formulation of sustainable development policies. This article aims to estimate the economic value of ecosystems in coastal areas based on spatial. The economic valuation method used is the benefit transfer method, the travel cost method, and the replacement cost method. Mapping the economic value of coastal ecosystems based on spatial using Geographic Information System (GIS). The economic value of the coastal area is divided into 3 zones, namely zone 1, in the northern part of the Bontang River estuary, amounting to IDR 21,85 trillion/year; zone 2, between the Bontang River estuary and the Blusu River estuary amounting to IDR 48,20 trillion/year; and zone 3, in the southern part of the Blusu River estuary, amounting to IDR 45,67 trillion/year. The economic value of ecosystems in coastal areas based on the spatial obtained can explain the value lost due to ecosystem disturbances more specifically and clearly in certain zones.